Proceedings of the Workshop on Physics of Superlattices and Quantum Wells, 17-21 October 1988, Shanghai, China (World Scientific, 1989)
"This volume contains important and active results in the fields of Superlattices and Quantum Wells. It includes current prospects regarding scientific discoveries and future device applications. Papers are contributed by leading scientists in the world."--